A binding motif for Hsp90 in the A chains of ADP‐ribosylating toxins that move from the endoplasmic reticulum to the cytosol. (5th July 2019) - Kellner, Alisha; Taylor, Michael; Banerjee, Tuhina; Britt, Christopher B.T.; Teter, Ken
Abstract: Cholera toxin (Ctx) is an AB‐type protein toxin that acts as an adenosine diphosphate (ADP)‐ribosyltransferase to disrupt intracellular signalling in the target cell. It moves by vesicle carriers from the cell surface to the endoplasmic reticulum (ER) of an intoxicated cell. The catalytic CtxA1 subunit then dissociates from the rest of the toxin, unfolds, and activates the ER‐associated degradation system for export to the cytosol. Translocation occurs through an unusual ratchet mechanism in which the cytosolic chaperone Hsp90 couples CtxA1 refolding with CtxA1 extraction from the ER. Here, we report that Hsp90 recognises two peptide sequences from CtxA1: an N‐terminal RPPDEI sequence (residues 11–16) and an LDIAPA sequence in the C‐terminal region (residues 153–158) of the 192 amino acid protein. Peptides containing either sequence effectively blocked Hsp90 binding to full‐length CtxA1. Both sequences were necessary for the ER‐to‐cytosol export of CtxA1. Mutagenesis studies further demonstrated that the RPP residues in the RPPDEI motif are required for CtxA1 translocation to the cytosol. The LDIAPA sequence is unique to CtxA1, but we identified an RPPDEI‐like motif at the N‐ or C‐termini of the A chains from four other ER‐translocating toxins that act as ADP‐ribosyltransferases: pertussis toxin, Escherichia coli heat‐labile toxin, Pseudomonas aeruginosa exotoxin A, and Salmonella enterica serovar Typhimurium ADP‐ribosylating toxin. Hsp90 plays a functional role in the intoxication process for most, if not all, of these toxins. Our work has established a defined RPPDEI binding motif for Hsp90 that is required for the ER‐to‐cytosol export of CtxA1 and possibly other toxin A chains as well.